Applied Linguistic Approach to Language Learning Strategies : (A Critical Review) - Dahlan Dahlan (P3I Luwu Raya, 2021)
From applied linguistic point of view, the fundamental question facing the language teachers, methodologists and course designers is which procedure is more effective in FL/SL: learning to use or using to learn? Definitely, in order to be a competent language user, knowledge of language system is necessary, but it is not sufficient to be a successful language user. That is why there was a gradual shift of attention from the teacher and method towards the language learner. Thus, there were changes in the conceptualizations of language competence and the mechanisms and strategies involved in the process of language learning. In this paper, the nature and specifications of language learning strategies, i.e., cognitive, metacognitive, linguistic and sociolinguistic strategies have been discussed; and the crucial role of metacognitive strategies has been emphasized in strategy-based instruction.